Developing, Modifying, and Validating a TaqMan Real-Time PCR Technique for Accurate Identification of Leishmania Parasites Causing Most Leishmaniasis in Iran - Fotouhi-Ardakani, Reza; Ghafari, Seyedeh Maryam; Ready, Paul Donald; Parvizi, Parviz (Frontiers in Cellular and Infection Microbiology, 2021)
Many laboratory methods are used to diagnose leishmaniasis because it is characterized by varied symptoms and caused by different Leishmania species. A quantitative real-time PCR method based on a TaqMan probe was developed and modified for accurate identification of human cutaneous leishmaniasis (caused by Leishmania major or Leishmania tropica) from endemic areas of Iran. Two gene regions of amino acid permease 3 (AAP3) and cytochrome oxidase II (COII) were considered. Six new sets of species-specific primers and probes were designed. A total of 123 samples were examined and employed to evaluate and validate real-time PCR. According to parasitic load of the genesig® Leishmania Advanced Standard Kit, a serial dilution of purified plasmid (2-2×107 copies/reaction) was prepared under the same conditions for both genes. Specific primers and probes were able to detect three and six parasite copies in AAP3 and COII genes, respectively besides were able to detect three copies of parasites for L. major and L. tropica. The sensitivity of the reference kit and our method were 98.7% and 98.1%, respectively, and specificity was 100% for detecting parasite genomes in all assays. Designed primers and probes performed well in terms of efficiency and regression coefficient. For AAP3 and COII genes respectively, the linear log range was seven and the correlation coefficient (R2) was 0.749 and 0.996 for the reference kit using the standard generated curve and 0.98 and 0.96 with serial dilutions of parasite DNA. This research detected L.major and L. tropica definitely and opens the horizon for the other scientists in the multiplex reactions in designing and optimization of the conditions in silico and in vivo.